(3GdUMjaI GdSLGOjIs - (3GdbQTj GdgGTej, CHh GdMSf, Rjf GdYGHOjf, Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH, (B94(3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3MOKfG GdSjO GdCLd fLe GdOjf HgGA GdTQa CHh GdMSf eMeO Hf GdMSf Hf CMeO Hf Ydj Hf eMeO Hf YeQ Hf jMji GdYdhj GdMSjfj QMeg Gddg bGd CNHQ GdTjN GdSYjO CHh YHO Gddg eMeO Hf CMeO Hf TgQjGQ GdNGRf (B...s
(3BNQgG (B:s
.. (3hJefMfj GdSdGeI aj Ojfj hfaSj hdG JhMT Hj Cgd CfSj hJJe GMSGfc ajeG Hbj ef YeQj ceG CMSfJ ajeG eVIi GMSGfc efg jG CQMe GdQGMejfs
(3JHUQI GdeDda (B:s
(3oJfSH dRjf GdYGHOjf Ydj Hf GdMSjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\277s
(3GdPQjYI (B15\95s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs